Step
*
1
of Lemma
p2J_symmetry
1. a : ℙ^2
2. b : ℙ^2
3. a ≠ b
4. b ≠ a
⊢ ∃m:{m:ℝ| m ≠ r0} . req-vec(3;p2J(a;b);m*p2J(b;a))
BY
{ (D 0 With ⌜r(-1)⌝  THEN Auto THEN D 0 THEN Auto) }
1
1. a : ℙ^2
2. b : ℙ^2
3. a ≠ b
4. b ≠ a
5. i : ℕ3
⊢ (p2J(a;b) i) = (r(-1)*p2J(b;a) i)
Latex:
Latex:
1.  a  :  \mBbbP{}\^{}2
2.  b  :  \mBbbP{}\^{}2
3.  a  \mneq{}  b
4.  b  \mneq{}  a
\mvdash{}  \mexists{}m:\{m:\mBbbR{}|  m  \mneq{}  r0\}  .  req-vec(3;p2J(a;b);m*p2J(b;a))
By
Latex:
(D  0  With  \mkleeneopen{}r(-1)\mkleeneclose{}    THEN  Auto  THEN  D  0  THEN  Auto)
Home
Index